Can Indonesia's Decentralized Education Technology Governance Policy: Evidence from Muslim Countries - Thoha, Mohammad; Syawqi, Abdul Haq; Yahaya, Mohammad Zaini; Septiadi, Dimas Danar; Hidayatulloh, M Haris (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2023)
Decentralization of education policies has been implemented in Indonesia and Malaysia; however, their potential impact on Islamic education technology innovation remains to be seen. Comparing and contrasting the Education Decentralization Policies of Malaysia and Indonesia is the objective of this study. This is normative legal research derived from tertiary, primary, and secondary legal sources. First, decentralization policies for the development of Islamic education technology are complicated, according to the research findings, because the Ministry of Education and Culture and the Ministry of Religion have a dualism of regulation and management that violates the concepts and spirit of regional autonomy. Second, regulatory dualism affects the quality of education in Indonesia, whereas integrated management is implemented in a single institution for education in Malaysia. Thirdly, Malaysia has endeavored since elementary school to integrate science and technology. Over the past decade, the Indonesian central government has implemented the Madrasah Reform program, among other initiatives and developments, to develop IT-based Islamic education.